MOLECULAR EPIDEMIOLOGY OF SMALL RUMINANT FASCIOLOSIS IN SELECTED REGIONS OF AZAD JAMMU AND KASHMIR - Ahmad; I. A. Z. Durrani; M. S. Khan; K. Ashraf; M. Avais; M. Ijaz; M. H. Saleem; M. Saeed; N. Ahmad; K. Hameed (Journal of Animal and Plant Sciences, 2017)
The present study was carried out to determine prevalence of Fasciolosis in sheep and goats at three different altitudes viz; <3000, 3000-6000 and >6000 feet above sea level in Azad Jammu and Kashmir (AJK). Rectal faecal samples from 4662 small ruminants (n=2242 sheep; n=2420 goats) were collected during the year 2012. The samples were examined by centrifugal floatation and sedimentation techniques while egg per gram (EPG) count was performed through McMaster technique. Prevalence of Fasciolosis in sheep and goats was 26.49% and 9.91%, respectively with an overall prevalence of 17.88%. The prevalence in both the species of animals was significantly different (P<0.05) at altitude <3000, 3000-6000 and >6000 feet. When compared, significant difference (P<0.05) was observed in different season, age groups and flock sizes. The intensity of infection (EPG) at different altitudes in sheep and goats was significantly different (P<0.05). It was concluded that Fasciolosis was prevalent in AJK with variable prevalence and intensity at different altitudes. Further studies are required to identify the Fasciola species involved in the disease in different species of animals in different climates for tactical control measures.
Keywords: Fasciolosis; Small ruminants; Altitudes; Azad Jammu and Kashmir